Innovation In the Use of Animated Videos in Arabic Language Learning - Adha, A. Dini Jumriana; Syarif, Maria Ulfah; Ahmadi, Maswan; Setiyawan, Agung (Abjadia : International Journal of Education, 2025)
The low interest of students in learning Arabic is one of the non-linguistic problems that have long challenged the effectiveness of Arabic language education. This occurs because many students perceive Arabic as a difficult subject that has little relevance to daily life, which makes the learning process less engaging. This study aims to examine the effectiveness of using animated video media as an innovative learning tool to increase students’ interest in learning Arabic among eleventh-grade language students at MAN 1 Bone. This research employed a quantitative approach with a one-group pretest–posttest experimental design, using interviews, observations, and questionnaires as data collection techniques. The findings indicate a significant increase in students’ learning interest after the implementation of animated video media, with the mean score rising from 58.83 (pretest) to 79.83 (posttest), showing an improvement of approximately 21 points. The effect size (Cohen’s d = 1.27) indicates a large practical effect, suggesting that the use of animated videos was not only statistically significant but also pedagogically meaningful in enhancing students’ interest in learning Arabic. This study highlights the importance of integrating technology-based instructional media into Arabic language education to align with the characteristics of the digital generation, who prefer visual and auditory interactive learning experiences.